“Evaluación de la calidad de los frutos de mango criollo y haden (Mangifera indiez L.) sometidos a tratamiento con agua caliente y almacenamiento postcosecha” - Montoya Salas, Mariela Cristina (2000)
With the purpose to evaluate the effect ofthe treatment with warm water in the Quality of the crop of Criollan Mangos and Haden (Mangifera indica L ), and to know its preservation in storage refrigerated and into and environmet. lt has taken place with croped and all riped fruits at the same time covering 10-20% of the fruit. This test was done at the Quality Control Laboratory of the Agroindustrial Engineering Faculty - National University of San Martín. The fruits carne from the commercial orchads of the Morales District to city of Tarapoto placed in wooden boxes (400x400x650 mm). The proof was done Mangos fruits with or without hot water at 46ºC x 5 minutes both proof were storaged under temperatures of 14ºC and of 28±2ºC of the Criollan and Haden simulating transport condition for Iquitos Market: The first day was considered the arrival at Yurimaguas (by land), the fourth day the arrival at !quitos city by river boat, the fifth day, a partial selling at the market was considered, the seventh day all the product were sold and on the fourteenth day to see to loss of weight and quality of the fruit. The result were lost of weight, resistence to pressure, solids, pH, acid sour. The fruits accepted during test lth, 4th, Sft, 7th and fourteenth day of storaged. Temperature was observed in 28±2ºC in the loss of weight since the fourth day until, the proof end reaching, 24.28% on fruits with immersión and 32.69% on fruits without immersion both for Criollan variety; 22.59% to fruits with immersion and 29.23% to fruits without immersion both for Haden variety. After the treatment with hot water wasn't observed statistics differences very important in the loss of weight, resistence of the pulp to pressure, solids, pH and % of acidity. *In the loss of weight, the fruits without immersion in hot water, Criollan variety and a temperature of 28±2ºC showed high percentage ofloss ofweight. *In the resistence of the pulp to the pressure of fruits with immersion Criollan variety at temperature of28±2ºCpresented less resistence to the pulp ofthe fruit. *For the solids fruits without immersion, Criollan variety and temperature of 28±2ºC showed percentage of solids. *F or the pH fruits with immersion, variety Haden at temperature of 14 ºC presented less pH. *For the percentage of acidity, fruits without immersion in hot water Haden variety at temperature of28±2ºC presented less percentage of acidity. It' s considered that the treatment with hot water doesn't alter the commercial Quality of the Criollan Mangos and Haden fruits to think about quality and to be accepted for selling, and long investigation, the fruits mantained its characteristics after a period of time of storage for 9 days at temperature 28±2ºC till 7 days at temperature 14ºC the fruits without immersion in hot water, mantain its characteristcs till 14 days of storage. The panel of tasting accepted all fruits that contain the following conditions. • Fruits with immersion and without immersion in hot water storage at temperatures 14 ºC and 28±2ºC. • All fruits storage with refrigeration without immersion in hot water from 4th, day until the end test.